The bazaar of bad dreams [large type] : stories - King, Stephen, 1947- (Thorndike Press, 2015)
"From a master of the short story, a collection that includes stories never before in print, never published in America, never collected and brand new- with the magnificent bones of interstitial autobiographical comments on when, why and how Stephen King came to write each story"--